Richard Sharpe Patterson papers - Patterson, Richard Sharpe, 1908-1976.; Dougall, Richardson, 1917-; Patterson, Richard Sharpe, 1908-1976.
Correspondence, writings, notes, research material, printed matter, wax impressions of seals, photographs, and other papers relating primarily to Patterson's research and writing on the Great Seal of the United States. Includes material pertaining to The Eagle and the Shield : A History of the Great Seal of the United States (1976) written by Patterson and Richardson Dougall. Also includes material concerning U.S. treaties, U.S. State Department buildings, portraits of U.S. secretaries of state, and U.S. State Department statistics.
Historian and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Department of State; Emblems, National -- United States; Public buildings; Treaties; United States -- Foreign relations; United States -- Seal; Authors; Historians